Allowance removal from green pieces as a method for improvement surface quality of advanced ceramics. (10th June 2018) - Sanchez, L.E.A.; Bukvic, G.; Fiocchi, A.A.; Fortulan, C.A.
Abstract: Advanced ceramics are usually machined after sintering in order to produce details and/or achieve the dimensional and geometric tolerances specified by project. However, this operation is neither cheap nor easy since it requires diamond tools, machine tools of high stiffness, and very low removal rates, even so, the finished parts might invariably contain critical defects. Machining of compacted ceramic powder before sintering, named green machining, is an alternative. This method does not require cutting fluid, presents great machinability, low energy consumption and few or no introduction of damages in the sintered workpiece. The single-action uniaxial pressing is the most used method for obtaining green ceramic pieces. Nevertheless it produces significant density variations in the outer regions of the piece, mainly located around the top and bottom edges, while the variation inside is smaller. The non-uniformity of density is considered responsible for distortion of the ceramic part during sintering. In this study, the distortion of the sintered workpieces was evaluated after green ceramic workpieces were machined using five different allowance values (1, 2, 3, 4, and 5 mm) in order to progressively remove the greatest density gradients. The distortion analysis was made on the top and bottom regions of the workpiece, where each upper and lower punch. operates, respectively. It was found that the distortion of the top region of the sintered workpieces was reduced about 97% when there was 5 mm of allowance removal and 82% for 1 mm of allowance. In the bottom region, the reduction was about 91% for removal of 5 mm of allowance and 48% for 1 mm. Cutting tool wear, cutting force, and surface roughness of green and sintered workpieces were also analyzed. In general, the influence of tool wear on surface roughness of sintered pieces and the correlation between surface roughness of the sintered pieces and the corresponding green ones were observed. Highlights: Compacted pieces have non-homogeneous density causing distortion after their sintering. The biggest non homogeneities are in outermost part, but can be removed by machining. Sintered piece machining involves much more damages and energy than green machining. The adequate amount of allowance and its removal improves the sintered piece quality. The control of cutting tool wear is important to reduce damages and surface roughness.